2010
DOI: 10.1245/s10434-010-1074-4
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Liver Function After the Cessation of Preoperative Chemotherapy for Colorectal Liver Metastasis

Abstract: The hepatic functional reserve, represented by the ICG R15 value, improves during the period after chemotherapy cessation. The present study suggests that chemotherapy cessation for at least 2-4 weeks enables an improvement in the hepatic functional reserve, especially among patients with an abnormal ICG R15 value (> 10%) who have received 6 or more cycles of FOLFOX and/or FOLFIRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 42 publications
2
41
1
1
Order By: Relevance
“…Moreover, in this trial, pre-treatment liver function in all enrolled patients was evaluated by the ICG retention test. Several published reports showed the usefulness of the ICG retention test in evaluating impaired liver function after NAC (30)(31)(32). In our study, although one patient could not tolerate the ICG retention test, ICG-R15 in the other patients was confirmed to be less than 20 and all patients were judged to be operable before enrollment.…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, in this trial, pre-treatment liver function in all enrolled patients was evaluated by the ICG retention test. Several published reports showed the usefulness of the ICG retention test in evaluating impaired liver function after NAC (30)(31)(32). In our study, although one patient could not tolerate the ICG retention test, ICG-R15 in the other patients was confirmed to be less than 20 and all patients were judged to be operable before enrollment.…”
Section: Discussionmentioning
confidence: 46%
“…Data on the normal range for ICGR15 test in patients with healthy liver or after chemotherapy are not available. It's know that the ICGR15 value is higher in patients pretreated with systemic chemotherapy [15] and also that ICGR15 value is closely related to the time between the measurement and the last chemotherapy administration [31]. In fact, Takamoto et al [31] found that ICGR15 values became normal four weeks after the end of chemotherapy, suggesting a recovery of the impaired liver function caused by the chemotherapy associated lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It's know that the ICGR15 value is higher in patients pretreated with systemic chemotherapy [15] and also that ICGR15 value is closely related to the time between the measurement and the last chemotherapy administration [31]. In fact, Takamoto et al [31] found that ICGR15 values became normal four weeks after the end of chemotherapy, suggesting a recovery of the impaired liver function caused by the chemotherapy associated lesions. Narita et al [16] included 18% of patients that didn't receive any preoperative chemotherapy and no data on time interval between the cessation of preoperative chemotherapy and ICGR15 test was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, indocyanine green clearance test [29] or hepatic scintigraphy [30] has also been reported to be a good indicator of hepatic functional reserve with regard to metabolic function. Because FLR volume itself is not correlated with functional reserve, dynamic measurements should be integrated to estimate the total functional reserve of FLR in individual patients.…”
Section: Technical Resectabilitymentioning
confidence: 99%